Fact, value, policy: Reading and writing arguments (McGraw-Hill, 1994)
The book divides argumentative discourse into three categories of claims: those of fact, value, and policy. It offers a brief overview of the relationships among these three categories; then, it discusses the categories of fact, value, and policy individually. Finally, the book addresses the writing process, including description of trategies of research, organization, and writing